Drastic Enhancement of Catalytic Activity via Post‐oxidation of a Porous MnII Triazolate Framework. Issue 36 (17th July 2014) - Liao, Pei‐Qin; Li, Xu‐Yu; Bai, Jie; He, Chun‐Ting; Zhou, Dong‐Dong; Zhang, Wei‐Xiong; Zhang, Jie‐Peng; Chen, Xiao‐Ming
Abstract MnIII is a powerful active site for catalytic oxidation of alkyl aromatics, but it can be only stabilized by macrocyclic chelating ligands such porphyrinates. Herein, by using benzobistriazolate as a rigid bridging ligand, a porous MnII azolate framework with a nitrogen‐rich coordinated environment similar to that of metalloporphyrins was synthesized, in which the MnII ions can be post‐oxidized to MnIII to achieve drastic increase of catalytic (aerobic) oxidation performance.